1992
DOI: 10.1212/wnl.42.6.1136
|View full text |Cite
|
Sign up to set email alerts
|

Neurolymphomatosis

Abstract: We describe a patient with sensorimotor peripheral neuropathy and cranial neuropathy due to autopsy-proven neurolymphomatosis defined by infiltration of peripheral nerves by tumor cells and review the findings in 39 previously reported patients. The cause of the neuropathy is not known. The association with immune-deficient states suggests virally mediated pathogenesis, possibly a retrovirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
101
1
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 0 publications
1
101
1
1
Order By: Relevance
“…Because these patients may have comorbid conditions such as diabetes (and diabetic neuropathy) or chemotherapy-induced neuropathy, the EMG findings may be misleading. 16,23 The premortem diagnosis is confirmed by nerve biopsy. The first case diagnosed by nerve biopsy was in 1975 by Vital et al 24 Before that, all cases were diagnosed at autopsy.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Because these patients may have comorbid conditions such as diabetes (and diabetic neuropathy) or chemotherapy-induced neuropathy, the EMG findings may be misleading. 16,23 The premortem diagnosis is confirmed by nerve biopsy. The first case diagnosed by nerve biopsy was in 1975 by Vital et al 24 Before that, all cases were diagnosed at autopsy.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, the first large series of NL was reported by Diaz-Arrastia et al, 16 who described 1 case and reviewed 39 other reported cases. Twentyeight patients (72%) presented with subacute progressive neuropathy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We considered sarcoidosis as the most plausible diagnosis, but could not initially rule out ML,because MLcan also present all of the above findings; Fever and lymphadenopathy are the most common signs of ML.MLcan affect the salivary glands, especially in patients with Sjogren's syndrome (8) and it has been reported that MLhas involved bilateral parotid glands (8,9). MLcan present a variety of neurological signs (10). Consequently, we measured serum ACE,sIL2R and TK, the markers of sarcoidosis and/or ML.…”
Section: Discussionmentioning
confidence: 99%